Effect of citrate concentration on colloidal gold (Au) nanoparticles produced using electro-dissolution-reduction method - Haiza, Haroon; Yaacob, Iskandar Idris; Ahmad Azhar, Ahmad Zahirani (Trans Tech Publications, 2016)
Colloidal gold nanoparticles have been successfully synthesized using electrodissolution-reduction process that consists of a simple two-electrode cells connected to a DC power supply. Throughout the process, bulk gold at the anode was oxidized into gold cations which then reacted with the chloride ions to form aurochloride complex. The complex ions were then reduced by the citrate ion to form colloidal gold nanoparticles. The size and shape of the nanoparticles were modulated by varying the citrate concentration. The colloidal gold nanoparticles obtained were characterized by field-emission scanning electron microscope (FESEM), transmission electron microscope (TEM) and ultraviolet-visible spectrophotometer (UV-Vis). From FESEM analysis, it was found that by increasing the citrate concentration, the size of colloidal gold nanoparticles produced marginally increased. The mean sizes of gold nanoparticles were roughly about 18.7 nm, 19.3 nm, 20.5 nm and 21.3 nm for citrate concentrations of 0.05 M, 0.10 M, 0.15 M and 0.20 M, respectively. However, sample prepared without the addition of citrate, remained colorless indicating that aurochloride complex ions were not reduced to colloidal gold nanoparticles. TEM micrographs showed that the shape of gold nanoparticles obtained is almost spherical. The characteristic peaks of UV-Vis spectra revealed that the suspension was indeed colloidal gold nanoparticles.